PERSEPSI MAHASISWA TENTANG KOMPETENSI MENGAJAR DOSEN PENGAMPU PADA MATA KULIAH STRUKTUR ALJABAR - Sutriningsih, Naning (JURNAL E-DUMATH, 2016)
Students perception about lecturer teaching ability of Aljabar Structural areobservation process, introduction, conclusion, and studentâs assessment aboutlecturer ability in learning management includes, comprehension towards students,planning and learning implementation, learning outcome evaluation and studentâsdevelopment ability in several competence actualization. The importance to findout the studentsâ perception of lecturer teaching competency by studentsâ learningperformance is 70% in Aljabar Structural subject during four year in low category.The objective of this study is knowing the studentsâ perception about lecturerteaching. Competency in the Aljabar Structural subject studentsâ perception datawas gotten by questionnaire whereas the studentsâ learning performance data wasgotten from studentsâ learning performance data was gotten from studentsâlearning outcome that documented in BAAK STKIP MPL. Furthermore, fromanalysis the data perception got 75,6% by using descriptive, the students got theperception in good categorize and very good about studentsâ competency ofAljabar Structural subject. It shown that students perception was not givesignificant contribution toward low students performance shown by contributionscore 2,69%.Keywords: Students perception, studentsâ learning performance,Aljabar Structural